SIGNIFICANCE OF PATHYA-APATHYA IN PRESENT ERA W.S.R.TO MADATYAYA - Sharma Poonam; Sharma Anita; Renu Sharma (International Journal of Applied Ayurved Research, 2020)
Wholesome food and lifestyle is very essential for maintaining good health. The food and regimen that are beneficial to Strotas or Dhatus and please the mind are considered as Pathya. Opposite to these are considered as Apathya. Both terms Pathya and Apathya are interchangeable in some conditions as it depends upon Kaal, Matra, Kriya, Deha, Dosha, Bhumi etc. factors. Judging from the various conditioning factors, even the most tasteful object might change to be unwholesome or vice-versa. Madatyaya refers to group of disorders caused due to improper and excessive intake of alcohol. Vyadhi-janaka nidan (Etiological factors) as heavy and prolonged use of alcohol against rules and regulations – vitiates Vata, Pitta and Kapha dosha and mainly affect Ojas. Chronic Alcoholism leads to nutritional deficiencies which affect organs of body and produce many diseases further. In management of nutritional deficiencies, Pathya-Apathya (dietary management) is itself a complete treatment. As nutritional requirement fulfilled by proper diet and person starts to follow rules of taking Madya as prescribed in Ayurveda, many symptoms of Madatyaya relieved. An attempt has been made in order to compile and concise Pathya – Apathya producing a prescribed diet and life style w.s.r. to Madatyaya.